ANALISIS HUKUM TERHADAP KEUANGAN BADAN USAHA MILIK NEGARA SEBAGAI KEUANGAN NEGARA - Radisman Saragih (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract Regulations governing the country’s nances embrace the state’s nancial concept in a broad sense, the state’s nances not only cover the nances in the BUDGET only, but also includes the BUDGET-separated to the government District (APBD), to the state-owned enterprises, to the BUMD and to other agencies and all State property assets that can be assessed by money. Thus, the nancial in the BUDGET and nancial that has been separated into nance APBD. Become a nancial BUMN, become nance BUMD, and become another nancial entity, as well as all state nances are a state nancial system. Act No. 17 year 2003 on state nances, Law No. 19 of 2003 on state-owned enterprises, Law No. 1 of 2004 concerning the national law on ¬ haration, Act No. 15 year 2004 on management inspections and other state nancial liabilities and statutory regulations, including the CONSTITUTION 1945 post-amendment which is the statutory regulation in the State nancial eld is including public law areas. Keywords: APBD; nance; constitution.